Affective communities : anticolonial thought, Fin-De-Siècle radicalism, and the politics of friendship - Gandhi, Leela, 1966- (Politics, history, and culture., 2006)
Investigates friendships between anti-colonial Indians and anti-imperial 'westerners' in late-19th and early 20th centuries, claiming that such inter-cultural collaborations need to be added to annals of non-violent historiography.